2010
DOI: 10.1016/j.metabol.2010.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ghrelin, growth hormone–releasing peptide–6, and growth hormone–releasing hormone on growth hormone, adrenocorticotropic hormone, and cortisol release in type 1 diabetes mellitus

Abstract: In type 1 diabetes mellitus (T1DM), growth hormone (GH) responses to provocative stimuli are normal or exaggerated, whereas the hypothalamic-pituitary-adrenal axis has been less studied. Ghrelin is a GH secretagogue that also increases adrenocorticotropic hormone (ACTH) and cortisol levels, similarly to GH-releasing peptide-6 (GHRP-6). Ghrelin's effects in patients with T1DM have not been evaluated. We therefore studied GH, ACTH, and cortisol responses to ghrelin and GHRP-6 in 9 patients with T1DM and 9 contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Intravenous administration of ghrelin stimulates GH release [43] which peaks at 5-15 min and returns to basal levels after 1h. Ghrelin administered intravenously is more potent than GH-releasing hormone (GHRH) in stimulating the release of GH in anaesthetised or freely moving rats, and in humans [44,45]. Intracerebroventricular injection appears to be a more potent route of delivery than intravenous administration.…”
Section: Action Of Ghrelin On Pituitary and Hypothalamusmentioning
confidence: 99%
“…Intravenous administration of ghrelin stimulates GH release [43] which peaks at 5-15 min and returns to basal levels after 1h. Ghrelin administered intravenously is more potent than GH-releasing hormone (GHRH) in stimulating the release of GH in anaesthetised or freely moving rats, and in humans [44,45]. Intracerebroventricular injection appears to be a more potent route of delivery than intravenous administration.…”
Section: Action Of Ghrelin On Pituitary and Hypothalamusmentioning
confidence: 99%
“…GHRP-2 is a potent growth hormone secretagogue and has been shown to stimulate the secretion of ACTH and cortisol in humans (32). In addition, the stimulating effects of GHRP-2 on ACTH release have been suggested to be mediated via CRH and/or AVP, or may occur independently of both peptides (33,34). These findings suggest that, in the present case, administration of GHRP-2 may have stimulated corticotroph cells via pathways other than the CRH receptor under conditions of full endogenous CRH stimulation.…”
Section: Hashimoto Thyroiditismentioning
confidence: 99%
“…The association of glycaemic control in T1D with fatty acid metabolism has been noted previously: hyperinsulinaemic euglycaemic clamp studies demonstrated that adolescents with T1D have significantly higher rates of lipolysis and endogenous glucose production and lower peripheral glucose uptake during hyperinsulinaemia compared to controls. 55 Higher rates of lipolysis, free fatty acidaemia 2 and glucose production could reflect combined effects of insulin deficiency, growth hormone hypersecretion 4 , 5 , 6 , 7 , 8 and/or hypercortisolaemia, 4 , 9 , 10 which are most apparent at times of severe metabolic decompensation. 56 Increases in availability of fatty acids may lead to mitochondrial overload and stress, 32 , 57 , 58 , 59 with consequent incomplete FAO 32 , 57 , 60 and decreased glucose oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…This in turn promotes lipolysis and proteolysis and decreases glucose uptake and utilisation. 2 , 3 Factors postulated to contribute to IR in T1D include free fatty acidaemia, 2 growth hormone (GH) hypersecretion, 4 , 5 , 6 , 7 , 8 hypercortisolaemia, 4 , 9 , 10 excess adiposity 11 and pubertal progression, especially in girls. 12 , 13 While the prevalence of obesity is increasing in individuals with T1D, studies have also demonstrated that normal‐weight adolescents and adults with T1D are less sensitive to insulin than controls without T1D with similar BMI.…”
Section: Introductionmentioning
confidence: 99%